ORGANIZING STUDENTS’ RESEARCH ACTIVITIES IN COMPETENCE-BASED FORMAT - Elena N. Barashko (Advanced Engineering Research)
Some questions of the building and development of the students’ research competence in the course of their exploration and research activities are considered. The principal stages of the training research activities and methodic environment providing the development of thinking, as well as building the students’ research competence, are presented.